Assessment of The Role of Human Resources in The Mediation of Possible Divergences of Ideas Among Multigeneration (Baby Boomers, X, Y, and Z) - Iqbal, Adnan; Trevisan, Felipe (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
In the current labour market with the increasingly technological and competitive situations, generations and their differences are being studied extensively in diverse cultures. Today, companies have about three to five generations working in the same teams and with different hierarchies. Faced with this scenario, companies benefit from different ideas and concepts, due to the fact that everyone can add their thoughts and references. Still, there are conflicts among people of different ages (and generations) who diverge their concepts when making a decision or arriving at a common agreement within the organisation. In this sense, the aim of this study is to identify the perceptions of the work team within company “A” concerning intergenerational coexistence and hierarchies at work. As well as this, it is crucial to understand what the principal characteristics of each generation are, the possible divergences between them in the labour market, and the importance of Human resources as a mediation between those conflicts. This study was characterized by exploratory research. The research strategy used a questionnaire with both open and closed questions. A group of 113 participants of employees of the company ‘A’ responded to the questionnaire from their own perspective regarding conflicts in the workplace due to the range of ages (and generational gaps). The results gave a clear idea that each generation regards their preference to work or avoid working with some different generations on their team and their reasoning. Another interesting result of this project was the perspective of what the Human Resources sector can do to minimise those conflicts.